1992
DOI: 10.1161/01.hyp.19.1_suppl.i90
|View full text |Cite
|
Sign up to set email alerts
|

Obese Zucker rats are normotensive on normal and increased sodium intake.

Abstract: The purpose of this study was to determine whether genetically obese Zucker rats have higher arterial pressures than lean littermates on normal and high sodium intakes. Mean arterial pressure was directly measured in chronically instrumented Zucker rats (six lean [weight, 345.8 +/- 8.0 g] and five obese [529.0 +/- 6.2 g]) for 2 weeks on both a normal (2 meq sodium/day) and high (6 meq sodium/day) sodium intake (7 days each). In addition, daily heart rate, water intake, urine output, urinary sodium excretion, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0
2

Year Published

1992
1992
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 0 publications
2
13
0
2
Order By: Relevance
“…9,[22][23][24] In contrast, the majority of studies using normoglycemic, hyperinsulinemic obese Zucker rats have found no increase in arterial pressure. 14,18 These results support the hypothesis that hyperglycemia contributes to hypertension in obese Zucker rats. It should be noted that most studies examining arterial pressure control in obese Zucker rats have not reported blood glucose concentrations, 7,8,10,12,13,[15][16][17] thus precluding an estimation of the contribution of glycemic levels to elevated arterial pressure.…”
Section: Discussionsupporting
confidence: 80%
“…9,[22][23][24] In contrast, the majority of studies using normoglycemic, hyperinsulinemic obese Zucker rats have found no increase in arterial pressure. 14,18 These results support the hypothesis that hyperglycemia contributes to hypertension in obese Zucker rats. It should be noted that most studies examining arterial pressure control in obese Zucker rats have not reported blood glucose concentrations, 7,8,10,12,13,[15][16][17] thus precluding an estimation of the contribution of glycemic levels to elevated arterial pressure.…”
Section: Discussionsupporting
confidence: 80%
“…Zucker rats have been described as being both hypertensive and normotensive. Several studies indicate that ZFR are hypertensive compared with phenotypically normal heterozygous insulin-sensitive ZLR (1,10,24,50), whereas other studies show a normotensive state of ZFR (30,35,36). Several studies (10,19,45,47) indicate higher levels of SNA in homozygous Zucker rats than in phenotypically normal heterozygous Zucker rats (fa/Ϫ), and it has been suggested that alterations in sympathetic function in obese Zucker rats can be tissue specific (30).…”
Section: Discussionmentioning
confidence: 99%
“…Homozygous Zucker rats are insulin resistant, hyperinsulinemic, and obese. Previous studies on the link between alterations of blood pressure and SNA in the presence of insulin resistance in this strain have yielded contradictory results (1,10,19,24,30,35,36,47,50) that might to be caused, in part, by limitations of the assessment of the degree of alterations of glucose kinetics.We showed previously in the spontaneously hypertensive rat (SHR) and its related control strain (33, 34) that a suitable characterization of the dynamics of glucose kinetics is obtained from the intravenous glucose tolerance test (IVGTT) interpreted with the minimal model (4, 16). On the other hand, an important index of SNA is provided by somatosympathetic reflexes, which are coordinated autonomic responses to activation of somatic afferents mediated by changes in sympathetic activity that cause a cardiovascular reaction to changes in the physical state of the body (14,40).…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…(28)(29)(30)(31)(32)(33)(34) Entretanto, estes animais podem não apresentar algumas anormalidades exibidas em humanos obesos, como hiperinsulinemia, hiperglicemia, hipertensão arterial e hipertrofia cardíaca. (35,36) A administração de uma dieta rica em gordura para roedores representa uma alternativa em modelos experimentais, uma vez que, reproduz muitas características da obesidade humana. (37,38) (19,(71)(72)(73) que, como referido anteriormente, pode ser causada por alterações nas proteínas do trânsito de cálcio miocárdico.…”
Section: -Introduçãounclassified